he impact of drug-loading factors on the solid-state form of ritonavir-mesoporous silica systems - Tanweer Al-Dagamin; Joseph P O'Shea; Abina Crean (British Journal of Pharmacy, 2022)
Among the formulation techniques used to enhance the solubility and dissolution rate of poorly, aqueous-soluble drugs, mesoporous silica drug delivery systems have shown promise. A range of processes are employed to load drugs onto silica and solvent-based approaches are widely employed. This study aims to understand the influence of drug concentration insolvent and drug-silica ratio on drug solid-state form and amorphization within silica. Ritonavir which belongs to BCS Class II was used as a model drug. Ritonavir was loaded into Syloid®244FP using a solvent evaporation method. Ritonavir loading percentage was calculated based on the assumption that the entire specific surface area of silica is exposed and available for drug adsorption. Ethanol solutions with 3 different ritonavir concentrations; 70%, 32% and 20% saturated solubility at 25°C were employed. Ritonavir was loaded into silica at 1:1, 1:2and 1:3 ritonavir:silica ratios. All systems included ritonavir loaded beyond monolayer surface coverage. Ritonavir- Syloid®244 FP formulations were characterised using DSC, PXRD, FT-IR, and TGA. The results showed that all ritonavir-Syloid®244 FP systems prepared contained ritonavir in a non-crystalline state.